Contesting and Negotiating Othering from Within: A Saudi Arabian Female Student's Gendered Experiences in the U.S. Issue 3 (3rd May 2020) - Song, Juyoung
ABSTRACT: This article discusses a Saudi female student's experiences in the United States over two years, focusing on the process of negotiating and constructing her gender identity. The analysis addresses her conflicts and struggles with Saudi gender ideologies in and out of classrooms. Examining the intra-group conflict concerning gender and culture in the framework of Othering, the article demonstrates that her resistance to Othering reflects the dynamic process of her identity negotiation and agency. Her conflicts and struggles in the process include: (1) validating her "new" gender identity using the very same source, Saudi religious nationalism that essentializes Saudi women's gender identity; and (2) shifting relationships with Saudi male members to ameliorate a marginalized racial position. The article elucidates how gender becomes a site at which cultural, religious, and national discourses and conflicts intersect and how it affects L2 learners' participation within and beyond minority communities.